2008
DOI: 10.1186/1471-2474-9-132
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and osteoarthritis in knee, hip and/or hand: An epidemiological study in the general population with 10 years follow-up

Abstract: Background: Obesity is one of the most important risk factors for osteoarthritis (OA) in knee(s). However, the relationship between obesity and OA in hand(s) and hip(s) remains controversial and needs further investigation. The purpose of this study was to investigate the impact of obesity on incident osteoarthritis (OA) in hip, knee, and hand in a general population followed in 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
333
3
32

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(382 citation statements)
references
References 24 publications
14
333
3
32
Order By: Relevance
“…In addition, their results differed from our with regard to the high prevalence of hip pain (54.5%) compared with that observed in our population (21.95%). This is in accordance with a study that did not find any association between BMI and the occurrence of hip osteoarthritis (20).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, their results differed from our with regard to the high prevalence of hip pain (54.5%) compared with that observed in our population (21.95%). This is in accordance with a study that did not find any association between BMI and the occurrence of hip osteoarthritis (20).…”
Section: Discussionsupporting
confidence: 81%
“…It has been demonstrated that weight gain is associated with adverse effects on the knees, such as pain, stiffness and functional changes (22). Additionally, it has reported that BMI > 30 kg/m² is an important risk factor for the incidence of knee osteoarthritis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, estudos mostram que a maior prevalência de sobrepeso e obesidade resultam em alta incidência da OA de joelho nessa população 12,13,17 . Justifica-se ainda a amostra feminina do presente estudo pelo fato de os sintomas da OA ocorrerem antecipadamente em mulheres 17 . Ismail et al 18 , examinando mais de 200 pacientes com OA de joelhos, encontraram que mais de 90% eram obesos ou com sobrepeso, sendo maior a prevalência no sexo feminino, em uma relação de 2,4:1 para o sexo masculino.…”
Section: Discussão E Conclusãounclassified
“…This is further supported by studies that find increased plantar pressure in the foot as obesity increases (18) and a reduction of pain with weight loss (19). The association of obesity with painful, nonweightbearing joints, such as the hand (20), is not in keeping with the mechanical overload pathway and suggests that the metabolic effect of obesity may be an important consideration systemically. Despite investigations into the significance of adipokines in other regions of the body (21,22), their association with foot pain has not been formally investigated.…”
Section: Introductionmentioning
confidence: 87%